Optimasi Desain Bangunan Pelengkap Bendungan dengan Metoda Simpson Luas Penampang (Simpson’s Rule) - Carlina Soetjiono; Sunarto Sunarto (KEAIRAN, 2005)
Design of headworks should be considered in the mitigation of hazards in Indonesia. Several aspects considered in design consist of design flood, influeczes to the structures, and the risk of earthquake. The external loads have a negative impact to the structures so the dimension of the structure should be bigger. In connection of the overdesign of structure, the cross section design should be optimum. The Simpson’s rule  is used to compute accurately the cross section area of the structure. This method is carried out by using the matematical of the existing condition and the reductions of the volume and the weight of the structures caused by the holes in the structures. Experimentally, the studies have been carried out in the Kalibumi weir and the tower of Cikukang dam. These studies present that the results of the stability analysis of the non orderly and non massive structures are quite satisfy. The out-come of the analysis is obtain the safety dams concerning with the program of safety dams in Indonesia.                            Keywords: optimum design, Simpson’s rule, head-works, dams, massive structurePermalink: http://ejournal.undip.ac.id/index.php/keairan/article/view/2733[How to cite: Soetjiono, C. dan Sunarto (2005). Optimasi Desain Bangunan Pelengkap Bendungan dengan Metoda Simpson Luas Penampang (Simpson’s Rule), Jurnal Keairan, 12 (2): 30-42]